Anti-Cyberbullying Educational Messages in the Short Film “Dunia Agnes” - Adi, Achwan Noorlistyo; Aziz, Fetawa Amanai; Ilham, Yanuar (Yayasan Sinergi Kawula Muda, 2024)
Cyberbullying has become a serious threat in the digital era, especially among teenagers. This research focuses on the representation of anti-cyberbullying educational messages in the short film “Dunia Agnes” uploaded on YouTube by Cerdas Berkarakterter Kemdikbud RI. This research aims to describe how denotation, connotation, and myth represent anti-cyberbullying educational messages in the film. The data collection is a documentation technique because the research’s object is a short film. The results showed that the short film “Dunia Agnes” successfully represented anti-cyberbullying educational messages through denotation, connotation, and mythical signs. Denotation representation is shown through scenes that explicitly describe forms of cyberbullying, its impact on victims, and the importance of social support and resistance to cyberbullying. Connotation representation is shown through the use of symbolism, colors, and music that reinforce the emotional and psychological messages. Mythic representation dismantles various misconceptions about cyberbullying, such as thinking of it as a mere “joke”. The short film “Dunia Agnes” as a whole provides a representation of anti-cyberbullying educational messages by depicting the negative impact of cyberbullying on victims, the importance of the role of social support for victims, and also the need to change people's perceptions so that they do not underestimate cyberbullying anymore.